The Molecular Basis of β-Thalassemia - Thein, Swee Lay (Cold Spring Harbor Laboratory Press, 2013)
The β-thalassemias are characterized by a quantitative deficiency of β-globin chains underlaid by a striking heterogeneity of molecular defects. Although most of the molecular lesions involve the structural β gene directly, some down-regulate the gene through distal cis effects, and rare trans-acting mutations have also been identified. Most β-thalassemias are inherited in a Mendelian recessive fashion but there is a subgroup of β-thalassemia alleles that behave as dominant negatives. Unraveling the molecular basis of β-thalassemia has provided a paradigm for understanding of much of human genetics.